The science of frozen embryo transfer, is modified natural cycle better? - Hassan Hamze; Wadad Alameh; Robert Hemmings; Wael Jamal; Amro Banan; Camille Sylvestre (Gynecological Endocrinology, 2025)
The aim of this study was to compare pregnancy, obstetrical outcomes and number of visits between patients undergoing frozen embryo transfer in artificial vs modified natural cycle. A total of 1207 frozen single embryo transfer cycles performed in 2022 were retrospectively studied. Patients older than 40, with recurrent implantation failure, and recurrent pregnancy loss were excluded. Patients were divided according to their age, BMI, AMH, and type of embryo transfer protocol. Patients in the modified natural cycle group were followed by ultrasound until triggering criteria met, then HCG trigger was scheduled, and the embryo transferred 7 days later. In the artificial cycle group, patients received estrogen supplementation after downregulation, and when the endometrium reached a thickness ≥ 7 mm an embryo transfer was scheduled following intramuscular progesterone administration for 5 days. A total of 649 patients were included in the study. A higher percentage of patients in the artificial cycle group had an initial positive B-hCG test result. The modified natural group had significantly better clinical pregnancy and live birth rates, mainly due to the significantly higher miscarriage rate observed in the artificial cycle group. There was no difference in the mean endometrial thickness between both groups. The number of visits was higher in the m-NC group. Patients with a m-NC protocol had a lower risk of hypertensive disorders of pregnancy (HDP), but a higher risk of gestational diabetes, though the results were non-significant. In conclusion embryo transfer in m-NC yielded a higher live birth rate, more frequent clinic visits, and lower chances of miscarriage.